PERAN SEKOLAH DALAM MENGEMBANGKAN MINAT BAKAT SISWA SMP N 1 COLOMADU - Nida, Dani Saifun; Abidin, Zaenal (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research aims to analyze the role of the principal in developing students' interests and talents at SMP N 1 Colomadu. Using a qualitative approach, this research collected data through interviews with school principals, teachers, and students, as well as direct observation of extracurricular activities at school. The findings of this research indicate that school principals play a significant role in creating a supportive environment for the development of students' interests and talents. By providing adequate support and resources, school principals facilitate students to develop their interests and talents through diverse and interesting extracurricular programs. The principal also collaborates with arts and sports institutions outside the school to provide opportunities for students to develop their interests and talents. The research results show that the role of the principal has a positive impact on the development of student's interests and talents at SMP N 1 Colomadu. Student participation and achievement in extracurricular activities increase, and students are able to develop their potential more optimally. This also has an impact on student motivation and learning satisfaction. This research provides a better understanding of the importance of the principal's role in developing students' interests and talents, as well as providing recommendations for improving the principal's role in other school contexts.